(untitled) (International Journal of Engineering and Computer Science, 2015)
The use of information and communication Technology (ICT) in everyday life is particularly more pronounced in teaching and learning situation. However, it is not without serious challenges to use computer in teaching and learning. Inspire of the need to use ICT in teaching and learning in modern world, the situation in Borno state is highly challenging. This study is designed to assess computer as an essential tool for teaching and learning in selected secondary schools within metropolis such as Shehu Garbai Government Secondary school, Namu Model secondary school, Ruby Springfield College Maiduguri and Lamisula Government Secondary school Maiduguri in Borno State which sample were selected for the research . The researcher adopted survey research method with the use of questionnaire. Based on the findings, it was revealed that majority of the respondents who are 114 respondents representing (57%) are females and most of them in JSS 3 and 46 respondents males representing (23%) are aware and have knowledge of the computer because e-examination was introduced to them in their curriculum in 2013/2014 and consideration were on them, knowledge and awareness on computer in the modern world is factual and majority of the tools used in learning is Wikipedia and Google and some recommendations were made; Government should provide all schools with alternative source of power to make all services available to the students and to enhance quick and easy usage of ICT facilities, Government should create seminar or program to improve teachers’ knowledge and skill in ICT and other software, encourage the need of high level learning skills to act, respond, learn and adjust to ever-changing circumstances as the world is increasingly growing complex success and prosperity will be linked to people’s ability to think, act, adapt and communicate creatively.